2017
DOI: 10.1002/chem.201703524
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular C−C Coupling between 1‐Methyl‐1,2,3‐Triazole and 2,2′‐Bipyridine or 1,10‐Phenanthroline in MoII Complexes

Abstract: Unsupported 1-methyl-1,2,3-triazole has been coordinated to {Mo(η -methallyl)(CO) (N-N)} (N-N=2,2'-bipyridine, bipy; or 1,10-phenanthroline, phen) fragments, yielding cationic complexes that can be regarded as metalated triazolium salts. Their reactivity towards a strong base led to the deprotonation of the C5-H group of the triazole moiety, followed by an intermolecular nucleophilic attack to the ortho CH group of a bipy or phen ligand affording cyclic, bimetallic dearomatized C-C coupling products. The react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…The reactions described above, in the presence of AgOTf, as well as those previously reported consisting of the deprotonation of cationic molybdenum­(II) triazole complexes, suggest a significant difference in the acidity of the C4–H and C5–H groups of the Metz ligand. A natural bond order (NBO) analysis of the non-hydrogen atoms of the Metz ligand of the cation of molybdenum­(II) in compound 1 reveals that the most favorable CH group for deprotonation is C5 because it displays a lower negative NBO charge than C4 (−0.046 vs −0.060), and also this position is less hindered than the C4 for attack by the base.…”
supporting
confidence: 76%
See 2 more Smart Citations
“…The reactions described above, in the presence of AgOTf, as well as those previously reported consisting of the deprotonation of cationic molybdenum­(II) triazole complexes, suggest a significant difference in the acidity of the C4–H and C5–H groups of the Metz ligand. A natural bond order (NBO) analysis of the non-hydrogen atoms of the Metz ligand of the cation of molybdenum­(II) in compound 1 reveals that the most favorable CH group for deprotonation is C5 because it displays a lower negative NBO charge than C4 (−0.046 vs −0.060), and also this position is less hindered than the C4 for attack by the base.…”
supporting
confidence: 76%
“…The high reactivity of the thus-formed species triggered an intermolecular nucleophilic attack on an o -CH group of a 2,2′-bipyridine (bipy) or 1,10-phenanthroline (phen) ligand (coordinated to the transition-metal atom), affording cyclic, dearomatized C–C coupling products (Scheme S1). The reaction described above can be considered to be an in situ generation of a strong nucleophile that attacks an electrophile present in the reaction medium, which is a bipy or phen ligand. Taking into account that transition-metal-coordinated bipy or phen in the vast majority of the known complexes do not act as electrophiles and the intermolecular character of the reaction, we reasoned that the presence of a better electrophile counterpart in the reaction medium, such as a metal fragment, would lead to a completely different reactivity pattern.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that 2,2′-bipyridine (bipy) and 1,10-phenanthroline (phen) coordinated to cationic fac -rhenium­(I) tricarbonyl fragments are not chemically inert ligands and can undergo, under mild conditions, the addition of internal nucleophiles generated, in most cases, by deprotonation of appropriately positioned coligands. In the particular case of the deprotonation of 1-methylimidazole (N-MeIm) coordinated to fac -{Re­(bipy)­(CO) 3 }, followed by the action of excess MeOTf, the pyridine ring contraction concomitant with C–N bond scission was obtained ([ A ] in Scheme ). As we have demonstrated more recently, this type of pyridine ring-opening process is favored by more electron-rich cis -rhenium­(I) dicarbonyl complexes, obtained from fac -{Re­(CO) 3 } species by carbonyl substitution by a more σ-donor trimethylphosphane ligand.…”
Section: Introductionmentioning
confidence: 99%
“…Outer‐sphere MeLi addition to coordinated bipy and phen ligands of fac ‐[Re(N‐N)(CO) 3 (PMe 3 )]OTf (N‐N=bipy, phen, Scheme 1 b) complexes [17b] suggests that chelate identity plays a role in the site‐selectivity of the addition. Unfortunately, the target of the few intermolecular additions to metal‐bonded bipy and phen reported were the most electrophilic α‐to‐N positions, [17b, 19] and nucleophilic additions to the β‐to‐N positions remain elusive. Whether or not the nature of the nucleophile can change the site‐selectivity of the addition to metal‐bonded bipy and phen remains unknown.…”
Section: Introductionmentioning
confidence: 99%